Effects of public hospital clerkship in rural and underserved areas in South Korea on medical students’ perceptions and career intentions: a pre–post study - Sejin Kim; Sunju Im; Wonjin Lee; Sang-Hwa Lee; Ho Joong Jeong; Sang Yeoup Lee; Jong-Tae Lee; Ji-Hyun Seo (Korean Journal of Medical Education, 2026)
Purpose: This study examined the short-term effects of a 2-week clinical clerkship program in rural and underserved public hospitals on medical students’ perceptions of public healthcare and their intentions to work in non-metropolitan public hospital settings.Methods: The Public Hospital Clinical Clerkship Program (PHCCP) was implemented for fifth- and sixth-year medical students from five medical schools in South Korea during 2023 and 2024. The program included clinical observation, mentoring by public hospital physicians, and exposure to community-based healthcare services. Students completed self-administered questionnaires before and after the program assessing perceptions of public hospitals and intentions to work in rural or underserved areas. Post-program satisfaction with program structure and components was also evaluated. Pre–post changes were analyzed using paired t-tests.Results: Paired pre- and post-program analyses included 24 students from the 2023 cohort and 36 students from the 2024 cohort. Students showed significantly increased intentions to work in public hospitals and rural or small-city settings after the program in both cohorts (all p